Historia polonistyki w Płowdiwie - Nowak, Iliana (Postscriptum Polonistyczne, 2020)
The article presents the history of Polish language, literature and culture studies at University ‘Paisyi Hilendarski’ in Plovdiv, Bulgaria. The beginnings of Slavic Studies at University of Plovdiv date back to 1978. In 1991 the separate profile of Polish Philology was formed. Nowadays the majority of the faculty are members of the Department of General Slavic Linguistics and the History of the Bulgarian Language.